Beliefs of women with a history of Previous Cesarean Section regarding Vaginal Birth after Cesarean: A qualitative study - Roghieh Bayrami; Roksana Janghorban (Mashhad University of Medical Sciences, 2021)
Introduction:Vaginal birth is considered a safe mode of birth for most women who have had a prior caesarean with a transverse incision. However, most women who had a previous caesarean rarely choose vaginal delivery. The present study was performed with aim to explain the beliefs of women with a history of previous cesarean section regarding vaginal birth after cesarean in order to provide some suggestions for future interventions to increase vaginal delivery. Methods: This qualitative study framed by the Theory of Planned Behavior was conducted in the governmental hospitals of Urmia, Iran in March-February 2017. Data were collected using 24  in-depth semi-structured individual interviews.  Participants were selected among  pregnant and postpartum women with a history of cesarean section through purposeful sampling, until data saturation was reached. Data were analyzed through directed content analysis approach using the MAXqda software (version 10). Results: The findings were grouped into three themes namely: "attitude towards vaginal birth after cesarean" (Vaginal birth as a fast and cost-effective method of delivery, sense of danger about maternal-fetal harm), "normative beliefs towards vaginal birth after cesarean" (the emphasize of important people towards vaginal birth after cesarean, women's impression of vaginal birth after cesarean in the community) and "control beliefs towards vaginal birth after cesarean" (Individual and social barriers and facilitator). Conclusion: Women's attitudes, subjective norms, and control beliefs influence choosing vaginal childbirth after cesarean section. Education based on the theory of planned behavior could be considered with the aim of promoting vaginal delivery after cesarean section.